Selfishness and Self-centeredness - Ivanhoe, Philip J. (Journal of Korean religions, 2018)
The primary aims of this article are to describe and make clear the philosophically related but distinct notions of selfishness and self-centeredness and show how the latter in particular relates to other characteristically East Asian ethical concerns about the self, virtue, spontaneity, and happiness. We work toward these aims by relying upon examples drawn from the neo-Confucian tradition and specifically from their discussion of self-centered desires (siyu 私欲). As will become clear, the neo-Confucian view, like other South and East Asian conceptions of self-centeredness, has both a metaphysical and an ethical component. The former part of this multi-faceted conception makes the package less plausible to many modern people who may still find the general idea and corresponding approach appealing and even inspirational. We shall, therefore, devote the latter sections of this chapter to describing modern variations on the neo-Confucian conception of self-centeredness that can stand apart and independent of their original metaphysical foundation, show how these offer plausible and powerful perspectives on a range of moral challenges, and present appealing ideals that can ground distinctive forms of life.